Conceptual Engineering and Sex - Valero, Iñigo (Filozofia Nauki, 2023)
Current debates on the nature of human biological sex often revolve around the question “Is sex binary?” In this paper, I argue that framing the debate in these terms is problematic as it already constitutes a significant theoretical commitment which results in oversimplistic characterizations of human sex. I argue, thus, that neither the positive nor the negative answer to the question “Is sex binary?” is satisfactory and that a more nuanced approach is required. More positively, I suggest that conceptual engineering provides promising tools to engage in this debate more fruitfully and transparently. Finally, I defend conceptual pluralism about human biological sex, the view according to which the term ‘sex’ may be legitimately paired with more than one concept of sex.